Improve Employee Productivity by Applying Green Human Resources Management and Increasing Employee Job Satisfaction - Rahma, Saura Jeane Aquar; Soegoto, Herman (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to analyze the impact of applying green human resources management and increasing employee job satisfaction improving employee productivity. The research was conducted at the Institute for Development of Applied Nuclear Science and Technology with the employees as the research subject. The data used in this research are primary in form of a questionnaire and secondary data obtained from various scientific literature such as academic journals, digital books, and various documents from the organization. Multiple Linear Regression was used to analyze the respondents’ answers with a total of 134 employees, and the hypotheses were tested using the t-test and f-test. The result shows that employee productivity was simultaneously positively and significantly affected by green human resources management and employee job satisfaction. Employee productivity was partially positively and significantly affected by green human resources management and employee job satisfaction, which means that employee productivity will improve by implementing the green human resources management and increasing employee job satisfaction. This research is expected to impact the improvement of employee productivity by implementing green human resources management to increase employee job satisfaction.